The renin–angiotensin system promotes arrhythmogenic substrates and lethal arrhythmias in mice with non-ischaemic cardiomyopathy. (4th November 2015) - Yamada, Chinatsu; Kuwahara, Koichiro; Yamazaki, Masatoshi; Nakagawa, Yasuaki; Nishikimi, Toshio; Kinoshita, Hideyuki; Kuwabara, Yoshihiro; Minami, Takeya; Yamada, Yuko; Shibata, Junko; Nakao, Kazuhiro; Cho, Kosai; et al.
Abstract: Aims: The progression of pathological left ventricular remodelling leads to cardiac dysfunction and contributes to the occurrence of malignant arrhythmias and sudden cardiac death. The underlying molecular mechanisms remain unclear, however. Our aim was to examine the role of the renin–angiotensin system (RAS) in the mechanism underlying arrhythmogenic cardiac remodelling using a transgenic mouse expressing a cardiac-specific dominant-negative form of neuron-restrictive silencer factor (dnNRSF-Tg). This mouse model exhibits progressive cardiac dysfunction leading to lethal arrhythmias. Methods and results: Subcutaneous administration of aliskiren, a direct renin inhibitor, significantly suppressed the progression of pathological cardiac remodelling and improved survival among dnNRSF-Tg mice while reducing arrhythmogenicity. Genetic deletion of the angiotensin type 1a receptor (AT1aR) similarly suppressed cardiac remodelling and sudden death. In optical mapping analyses, spontaneous ventricular tachycardia (VT) and fibrillation (VF) initiated by breakthrough-type excitations originating from focal activation sites and maintained by functional re-entry were observed in dnNRSF-Tg hearts. Under constant pacing, dnNRSF-Tg hearts exhibited markedly slowed conduction velocity, which likely contributes to the arrhythmogenic substrate. Aliskiren treatment increased conduction velocity and reduced the incidence of sustained VT. These effects were associated with suppression of cardiac fibrosis and restoration of connexin 43 expression in dnNRSF-Tg ventricles. Conclusion: Renin inhibition or genetic deletion of AT1aR suppresses pathological cardiac remodelling that leads to the generation of substrates maintaining VT/VF and reduces the occurrence of sudden death in dnNRSF-Tg mice. These findings demonstrate the significant contribution of RAS activation to the progression of arrhythmogenic substrates.